Synthesis of graphene oxide nanofluid based micro-nano scale surfaces for high-performance nucleate boiling thermal management systems - Shoukat Alim Khan (14778226) (2021)
The objective of this study is to explore the exceptional thermal management ability of Graphene Oxide (GO) nanofluid and microporous surfaces (M) for nucleate pool boiling based thermal management systems. The performance of the designed system has been analyzed for thermal management of concentrated photovoltaics (CPV) system. A detailed analysis has been performed for GO nanofluid, with concentrations; 0.0001%, 0.001%, and 0.01%, and deionized (DI) water-based working fluid over the plane unmodified surface (P) and microporous (M) surfaces. GO nanofluid enhanced critical heat flux (CHF) and the heat transfer coefficient (HTC) over the plane surface. However, over M surface, GO nanofluid resulted in thick layer formation and significantly affected the NBHT performance. The highest CHF of 1850 kW/m2 has been observed for GO over the plane surface, increasing 2.31 times. M surface with deionized water resulted in the highest average HTC of 64.36 kW/m2.K, increasing 3.47 times. GO over the plane surface (Np) based NBHT thermal management system resulted in the highest concentration ratio of 3102 and can be used for CPV system. In comparison, M surface-based thermal management system resulted in the highest efficiency. Other Information Published in: Case Studies in Thermal Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.csite.2021.101436